THE COMPENSATORY GROWTH RESPONSE OF BROILER CHICKS BY USING EARLY QUALITATIVE FEED RESTRICTION PROGRAM - mi El-Khatib; Faiyz S; Ibrahim Said Kloor (Mesopotamia Journal of Agriculture)
The feasibility of broiler chicken over the phenomenon of compensatory growth after attesting to make its growth slow by using early qualitative feed restriction program had been studied , and its Impact on the qualities of productivity characteristics . The study included experiment with three levels of early qualitative feed restriction during (8-21 days) as well as on the treatment of control ad libtum then all the birds brought to feed free for the remainder of the study ( at the end of the 7 th week ) each levels included three replicates each of 25 birds for a replicate (75 birds / treatment) . Results of this experiment can be summarized as follows of feed for birds fed treatment 10% sawdust as comparison with control grow, while it showed a significant decrease in body weight of birds fed 30% diluted with soft wood sawdust , a significant decrease in the proportion of total mortality for all levels of restriction . With a decline in the values of the two criteria mentioned for the treatment of 30 % soft sawdust as compared with control at the age of marketing.